Exceptional Conditions for Favorable Neurological Recovery After Laminoplasty in Cases with Cervical Myelopathy Caused by K-line (−) Ossification of Posterior Longitudinal Ligament. Issue 15 (1st August 2021) - Tsujimoto, Takeru; Endo, Tsutomu; Menjo, Yusuke; Kanayama, Masahiro; Oda, Itaru; Suda, Kota; Fujita, Ryo; Koike, Yoshinao; Hisada, Yuichiro; Iwasaki, Norimasa; Takahata, Masahiko
Abstract : Study Design: A retrospective observational study. Objective: To clarify the exceptional conditions for a favorable neurological recovery after laminoplasty (LMP) for cervical myelopathy caused by K-line (−) ossification of the posterior longitudinal ligament (OPLL). Summary of Background Data: The K-line-based classification of cervical OPLL was developed to predict insufficient neurological recovery after LMP. For patients with K-line (−) OPLL, LMP generally yields the least improvement because of inadequate decompression of the spinal cord; however, there are some exceptional cases wherein LMP promotes favorable neurological recoveries. Methods: We retrospectively reviewed the medical records of 106 consecutive patients who underwent LMP for cervical OPLL to determine the demographic data, radiographic findings, and neurological recoveries of the patients as assessed preoperatively and 2 years postoperatively by their Japanese Orthopedic Association (JOA) scores. The factors associated with favorable outcomes after LMP in patients with K-line (−) were then investigated. Results: Of 106 total patients, 31 were classified as K-line (−), of whom 21 achieved the least neurological recovery after LMP (JOA recovery rate <50%), while the remaining 10 patients achieved favorable outcomes (JOA recovery rate ≥50%). Among the K-line (−) group patients, those with ext-K-line (+), which changed to K-line (+) in the neck-extended position, and the patients with up-K-line (−), in whom the lesion responsible for myelopathy in the upper cervical spine (C3 or above), showed favorable neurological recoveries after LMP. Conclusion: Our data shows that, even for patients with K-line (−) OPLL, a favorable neurological recovery can be expected after LMP in cases in which the OPLL is in the upper cervical spine or the K-line changes to (+) in the neck-extended position. This means that K-line-based predictions of surgical outcomes after LMP should be indicated for patients with OPLL in the middle and lower cervical spine with limited extension mobility. Level of Evidence: 4 Abstract : For patients with K-line (−) OPLL, the least improvement is generally seen after laminoplasty because of inadequate decompression of the spinal cord but favorable neurological recovery can be seen in cases with K-line (+) in the neck-extended position or whose lesion responsible of myelopathy was in the upper cervical spine.